2016
DOI: 10.5539/ibr.v9n9p78
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Ethics and Relationship Marketing - An Empirical Study that Measure the Effect of Ethics Practices Application on Maintaining Relationships with Customers

Abstract: The purpose of this study is to measure the effect of ethics embedded practices on maintaining long-term relationships with customers. Based on an extensive literature review, four elements of marketing ethics, namely, honesty, autonomy, privacy and transparency were identified and examined by utilizing a sample of 360 participants. Adopting a quantitative approach, the study conducted on telecommunication sector subscribers revealed that the elements of marketing ethics affected an organization's ability of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 33 publications
0
14
0
2
Order By: Relevance
“…Based on the initial findings of academic studies, a model was developed, and it showed that service quality, customer satisfaction, and bank image have a positive and direct effect on customer loyalty [17][18][19][20]. The researcher was able to establish that the three variables that were being studied have an impact on customer loyalty and will affect the rate at which a customer recommends a certain bank to his friends and family.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the initial findings of academic studies, a model was developed, and it showed that service quality, customer satisfaction, and bank image have a positive and direct effect on customer loyalty [17][18][19][20]. The researcher was able to establish that the three variables that were being studied have an impact on customer loyalty and will affect the rate at which a customer recommends a certain bank to his friends and family.…”
Section: Resultsmentioning
confidence: 99%
“…Emirates has developed its vision and values as follows: A strong and stable leadership team, ambitious yet calculated decision-making, and ground-breaking ideas all contribute to the creation of great companies. Of course, these have played a significant part in the development and growth of Emirates, and it is believed that business ethics and customer focus are the foundations on which the success has been built [89] [90]. Strong brand awareness through sponsorship of sports and games, caring for their employees and stakeholders, as well as the environment and the communities Emirates serve, have played a huge part in its past and will continue to signify its future.…”
Section: Current Leadershipmentioning
confidence: 99%
“…Since first impressions or getting it right the first time is essential (Lockwood, 1994;McDougall and Levesque, 2000), anticipating or aiding the decision making process of subscribers, especially those that consider various service providers could prove very valuable to service marketers. Subscribers might choose a network base on its service quality and price (Melody, 2001), contract features (Alshurideh, 2016) geographical areas, and multiple products (Chan-Olmsted and Jamison, 2001), loyalty program, quality ratings.…”
Section: Introductionmentioning
confidence: 99%